(untitled) (Mugda Medical College Journal, 2022)
Background: Health related quality of life (HRQoL) covers the impact of the disease or medical actions on the physical symptoms, functional status, and mental and social functioning. The KDQOL is a kidney disease–speciûc HRQoL instrument used in research. Objective: To observe the quality of life parameters in patients on continuous ambulatory peritoneal dialysis (CAPD). Methods: This cross-sectional study was carried out in three tertiary renal care hospital. Total 40 CAPD patient were selected as cases and 40 healthy individuals were included as controls. A semi-structured questionnaire was developed in English and translated to Bangla. The questionnaire contained questions related to: 1) KDQoL-36 developed by RAND; 2) Clinical and 3) laboratory parameters. Different clinical and laboratory parameters were evaluated. Quality of life (QOL) parameters were assessed by KDQOL-SF-36(V-1.3) questionnaire. The scoring procedure for the KDQOL-SF-36 first transforms the raw precoded numeric values of items to a 0-100 possible range. Higher transformed scores better quality of life. Results: Mean age of the study subjects was 55±11and control 56±11years (p=.0.664). They were also matched for sex and BMI. The main primary disease responsible for ESRD was diabetic nephropathy (57.5%), followed by glomerulonephritis and hypertensive nephropathy. Mean haemoglobin of the study subjects was 8.1±1.4 g/dl, albumin 3.1±1.4 g/dl and Kt/V 1.8±0.3. Mean physical composite score (PCS) calculated by KDQOL-SF-36 in CAPD and control group were 44±15 and 79±12 (p<0.001) and mean mental composite score (MCS) were 45±17 and 80±10 (p<0.001). When QOL parameters were compared between two groups according to Kt/V d”1.7 and >1.7 showed most of the scores were higher in Kt/V >1.7. Conclusion: Quality of life parameters among patients on CAPD were good; hence, it can be a viable option for ESRD patients in Bangladesh. Mugda Med Coll J. 2022; 5(1): 14-18